Dissolution of Germanium in Sulfuric Acid Based Solutions. (11th September 2015) - Gan, Nobuko; Ogawa, Yuichi; Nagai, Tatsuo; Masaoka, Toru; Wostyn, Kurt; Sebaai, Farid; Holsteyns, Frank; Mertens, Paul W.
Abstract : The phenomenon and mechanism of germanium (hereinafter Ge) dissolution in sulfuric acid based solutions were studied. The sulfuric acid concentration, the presence of an oxidizer and the treatment time were varied as parameters of these tests. It was clarified that Ge surface is covered by two layers: germanium dioxide (hereinafter GeO2 ) and germanium monoxide (hereinafter GeO). GeO2 dissolves easily in water and in the sulfuric acid solutions with high water fraction. On the other hand, the dissolution of GeO and Ge is influenced strongly by the sulfuric acid concentration in the solution and the treatment time when oxidizer is present in the solution.